If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 10 = 12x + -90 Reorder the terms: 10 + 8x = 12x + -90 Reorder the terms: 10 + 8x = -90 + 12x Solving 10 + 8x = -90 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 10 + 8x + -12x = -90 + 12x + -12x Combine like terms: 8x + -12x = -4x 10 + -4x = -90 + 12x + -12x Combine like terms: 12x + -12x = 0 10 + -4x = -90 + 0 10 + -4x = -90 Add '-10' to each side of the equation. 10 + -10 + -4x = -90 + -10 Combine like terms: 10 + -10 = 0 0 + -4x = -90 + -10 -4x = -90 + -10 Combine like terms: -90 + -10 = -100 -4x = -100 Divide each side by '-4'. x = 25 Simplifying x = 25
| 24x-50=4x-20 | | 9(4x+1)= | | -7a+50=-6-7(6+3a) | | 20x+30=10x+90 | | x^3+14x^2+49x=0 | | 2x+51.5=4x+3 | | 8(1-p)=-24-4p | | x^3-15=0 | | y=0.2192x+15.29 | | 100+14r= | | 0.2192x+15.29= | | 2x+4/3+54= | | R=100 | | 5(4x-6)-3x=47+6x | | 2+8+9+6-87-654-9+87654= | | 0.2187x+15.67= | | -2(4s-1)-2=-2(6s+7)-3 | | -(6z+2)(2-8z)+(-7z-6)(2-2z)= | | 3y=12-y | | 2x+20=70 | | x^2+15x+11=2x-1 | | 5.6-.32x=1.12 | | x^2+10x+18=9 | | 140-2x=34x+20 | | y=0.2187x+15.67 | | 3sinx+cosx=2 | | 12-9x=23-16x | | 57.99+.11x=58.54 | | (5b-3)(2b-6)-(-3+8b)(4b-4)= | | .23x+2.34=6.25 | | 4f-12=16 | | 4x^2-9x+9=7x+2 |